PERAN SOSIOLOGI BAGI PERKEMBANGAN KARAKTER PESERTA DIDIK DI SEKOLAH - Sergiopanus Parfin (SocioEdu: Sociological Education, 2020)
This study aims to explain the application of character education in learning sociology, and the role of sociology in the character development of students in school. The method used in this study is a qualitative method using discourse analysis. The results of this study indicate that the application of character education through sociology learning in schools is carried out through the integration of values and norms and material on multicultural societies in schools. The application of character education is also carried out through the application of learning tools that support the character development of learners at schools. The role of sociology for character development can be done through learning materials and sociology teachers because sociology itself is one of the subjects that discusses the material values and norms so that it helps in the development of students character at school.